Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

The question asks for sum of
1-x^2+X^3-X^4+x^5-X^6
In effect it is a geometric progression after 1 each term being multiplied by -X
so 1-(X^2-X^3+X^4-X^5+X^6) =1- Sum of geometric progression

Sum of geometric progression =a(1-r^n)/1-r

Where a= the first term which in this case is X^2
And r = the common ratio which in this case is â€“X
And n=the number of terms which in this case is 5 (X^2-------X^6)
So substituting we get
S=X^2 (1+X^5) /1+X in other words 49x 16808/8

The question asks for sum of 1-x^2+X^3-X^4+x^5-X^6 In effect it is a geometric progression after 1 each term being multiplied by -X so 1-(X^2-X^3+X^4-X^5+X^6) =1- Sum of geometric progression

Sum of geometric progression =a(1-r^n)/1-r

Where a= the first term which in this case is X^2 And r = the common ratio which in this case is â€“X And n=the number of terms which in this case is 5 (X^2-------X^6) So substituting we get S=X^2 (1+X^5) /1+X in other words 49x 16808/8

=49x2101=102949 1-S=1-102949=-102948

Hmm, I've never seen this formula before. Great job tho Can anybody enlighten us with this formula?
_________________

Don't be afraid to take a flying leap of faith.. If you risk nothing, than you gain nothing...

The question asks for sum of 1-x^2+X^3-X^4+x^5-X^6 In effect it is a geometric progression after 1 each term being multiplied by -X so 1-(X^2-X^3+X^4-X^5+X^6) =1- Sum of geometric progression

Sum of geometric progression =a(1-r^n)/1-r

Where a= the first term which in this case is X^2 And r = the common ratio which in this case is â€“X And n=the number of terms which in this case is 5 (X^2-------X^6) So substituting we get S=X^2 (1+X^5) /1+X in other words 49x 16808/8

=49x2101=102949 1-S=1-102949=-102948

Hmm, I've never seen this formula before. Great job tho Can anybody enlighten us with this formula?

The question asks for sum of 1-x^2+X^3-X^4+x^5-X^6 In effect it is a geometric progression after 1 each term being multiplied by -X so 1-(X^2-X^3+X^4-X^5+X^6) =1- Sum of geometric progression

Sum of geometric progression =a(1-r^n)/1-r

Where a= the first term which in this case is X^2 And r = the common ratio which in this case is â€“X And n=the number of terms which in this case is 5 (X^2-------X^6) So substituting we get S=X^2 (1+X^5) /1+X in other words 49x 16808/8

=49x2101=102949 1-S=1-102949=-102948

Good approach,

I was looking for short cut but ended up calculating 7*6 good things is you only have to multiply 6 times!!! and I had to redo it only twice...